Substituição parcial de cloreto de sódio na elaboração de filé de tilápia do nilo (oreochromis niloticus) salgado e seco. - Silva, Josivania Ribeiro da (2015)
The objective of this research was to quality evaluate Tilapia fillets, salted and dry, made by hand, with partial replacement of sodium chloride, by two methods of salting: dry salting and wet salting. Nile Tilapia (Oreochromis niloticus), which is a lean species, and Potassium Chloride (KCl) were used as a substitute for Sodium Chloride (NaCl). A completely randomized design (DIC) was used with two types of salting, three different levels of sodium chloride and potassium chloride and three repetitions totaling 18 samples. After microbiological evaluation, according to the recommendation of RDC nº 12 (BRASIL, 2001), salted and dry fillets were subjected to physical-chemical analyzes (moisture, ash, proteins, lipids, carbohydrates, pH, acidity, water activity and levels of sodium and potassium in muscle and brine) to verify the influence of factors on the quality of the samples. In the physical-chemical analysis, the results demonstrated that the partial substitution by potassium chloride in the salting mechanism significantly influenced most of the evaluated factors, a fact not observed in the microbiological analyzes. The experiment made it possible to reduce NaCl by 20% without significant changes in product quality. It shows that salty and dry tilapia files with a reduction in NaCl contents have excellent commercialization potential. Because it is a differentiated product with reduced sodium content.